The marketing information system of the greek shipping company - Plomaritou, Dr. Evi I. (SPOUDAI Journal of Economics and Business, 2008)
This article titled “The Marketing Information System (MIS) of the Greek Shipping Company”, presents the MIS that should be ideally followed by companies, which are activated in merchant shipping. The article describes the characteristics of the MIS’ subsystems, such as the internal file, the marketing information, the marketing research and the marketing decision support subsystem. Additionally, the article attempts a comparative analysis of the MIS that is applied in bulk and liner shipping companies. From bulk shipping, the tanker shipping companies were chosen and from liner shipping, the container shipping companies were chosen for investigation. The paper presents the results of the quantitative research that was carried out in 2005 concerning the Marketing Information System of the Greek Shipping Companies. JEL Classifications: Μ31, Ν70